Can prophylactic cranial irradiation of extensive-stage small cell lung cancer prolong survival? - Harada, Hideyuki (Therapeutic Radiology and Oncology, 2018)
Approximately 10% to 15% of lung cancers are small cell lung cancers (SCLCs). SCLC is divided into two subpopulations—limited-stage (LS) SCLC and extended-stage (ES) SCLC. In LS SCLC, all the lesions are inside the ipsilateral thorax. Lesions beyond this site are categorized as ES SCLC. Prophylactic cranial irradiation (PCI) is considered as the standard of care in patients with LS SCLC who achieve complete response after initial chemotherapy or thoracic radiotherapy. In SCLC, the brain is a common site of distant metastasis.